A REVIEW OF THEORETICAL BACKGROUND OF ADVENTURE TOURISM AND ITS DEVELOPMENT - Tilovmurodov Dostonbek (Web of Journals Publishing, 2024)
An examination of the current literature on adventure tourism reveals that research on the issue has thus far been primarily based on scholars’ and practitioners’ preexisting conceptions. This article contends that the subjective experience of adventure, as well as individual perceptions of what comprises it, must be examined and considered in the study of adventure tourism. Qualitative research methodologies should receive more attention in their examination. The planned shift in focus on people’s perceptions of adventure also calls into question the association of adventure tourism with only particular market segments and independent travelers. Further research, adventure tourism motive, and the ramifications for tourist behavior are examined.
Keywords: tourism industry, adventure tourism, tourism theory, tourism literature, tourism development, adventure tourism, adventure tourism motivation.